1991
DOI: 10.1093/oxfordjournals.jbchem.a123431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acetylpolyamines on In Vitro Protein Synthesis and on the Growth of a Polyamine-Requiring Mutant of Escherichia coli

Abstract: The functions of acetylpolyamines were examined with respect to stimulation of protein synthesis and cell growth. Unlike polyamines, acetylpolyamines could not lower the optimal Mg2+ concentration of protein synthesis, and the degree of stimulation of protein synthesis by acetylpolyamines was small. The addition of N1-acetylspermine did not stimulate cell growth of a polyamine-requiring mutant of Escherichia coli MA261, although acetylspermine was accumulated in the cells. Acetylspermine did not interfere with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 0 publications
3
27
0
2
Order By: Relevance
“…Our evidence suggests that acetylation occurs at low temperature to prevent excess spermidine from inhibiting the binding of Mg 2ϩ to the ribosome. Consistent with this is the finding that acetylpolyamines cannot substitute for polyamines in binding to RNA (18). Although the acetylpolyamine is still cationic, it has been suggested that the acetyl group may present a steric hindrance to the binding of nucleic acids.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Our evidence suggests that acetylation occurs at low temperature to prevent excess spermidine from inhibiting the binding of Mg 2ϩ to the ribosome. Consistent with this is the finding that acetylpolyamines cannot substitute for polyamines in binding to RNA (18). Although the acetylpolyamine is still cationic, it has been suggested that the acetyl group may present a steric hindrance to the binding of nucleic acids.…”
Section: Discussionmentioning
confidence: 64%
“…An effect of polyamines in in vitro translation is the lowering of the Mg 2ϩ requirement (18). Since spermidine binds to sites on the ribosome similar to those bound by Mg 2ϩ , it can replace ribosome-bound Mg 2ϩ (5,28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal accumulation of polyamine, however, can lead to inhibition of cell growth and protein synthesis (29); therefore, polyamine concentration should be regulated strictly and promptly to maintain optimum cell growth. It was reported previously that N-acetylpolyamine had less effect on growth and protein synthesis than non-acetylated polyamine (30), and a pathway to synthesize N-acetylpolyamine to decrease the toxicity of excess polyamine exists in both prokaryotes and eukaryotes (6,31). Because the ␥-glutamylation of putrescine by PuuA is similar to the acetylation of polyamines, it is predicted that PuuA also plays a role in detoxifying excess polyamine.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike spermidine, N-acetylspermidine is physiologically inert and does not bind to RNA or stimulate in vitro translation. Therefore, active conversion of spermidine to N-acetylspermidine by spermidine acetyltransferase would be an effective mechanism to reduce the toxicity associated with high levels of spermidine (Kakegawa et al, 1991). Although speculative, it is possible that cell density-dependent changes in intracellular spermidine levels, which are linked to methionine utilization and the production of S-adenosylmethionine (SAM), function as a metabolic sensor for B. pseudomallei to regulate gene expression and protein synthesis in a growth phase-dependent manner.…”
Section: Discussionmentioning
confidence: 99%